Kidney triplication with ectopic ureterocele: a case report - Osipov, I. B. (BMC Urol, 2020)
BACKGROUND: Kidney triplication is a rare urological abnormality. Association of triplex kidney and ureterocele is out of ordinary. Treatment of such patients usually implies heminephrureterectomy of the upper moiety. We report a case of a saved function of the upper moiety after minimal invasive surgical procedure. CASE PRESENTATIONS: 5-year old girl complained for continuous wetting. Examination revealed 3 - segmented left kidney with pelvi-ureteric dilation of the upper moiety, IV grade vesicoureteral reflux in the upper moiety, cervical ectopic ureteral orifice of the upper moiety and a commune ureteral orifice of the lower segments. An endoscopic laser dissection of ureterocele was performed. Drainage of the upper moiety of triplex kidney was restored. Examination 18 months later showed no wetting and infection symptoms. Pelvi-ureteric dilation of the upper moiety and cavity of ureterocele decreased to minimal. Grade of vesicoureteral reflux decreased to I. CONCLUSION: Minimal invasive elimination of obstruction of the upper moiety of triplex kidney was successful and led to regress of vesicoureteral reflux, urinary incontinence and let to avoid heminephrectomy.